A Linguist's Field Note - Caron, Bernard (Africas: Languages, History and Arts, 2003)
Around the word "field" come to crystallise contrasting views, debates, sometimes unnecessary disputes about what should be a specific type of linguistics by its methodologies and its objectives. It appears, however, to be more legitimate to associate it with the manner of being a linguist when, at certain moments, the discovery of a language cannot be dissociated from the discovery of the space where this language is inscribed. The discovery then has to do with techniques, certainly, but also with landscapes, meetings, risks, and (why not?) with adventures, to the point where the linguist gets lost. In 1990 Bernard Caron arrived, in the north of Nigeria on the trail of Zaar, a language that was numerically the most important of the group of Chadic languages about which precious little was known. This is the story of his research.